Mass screening of rice mutant populations at low CO2 for identification of lowered photorespiration and respiration rates - Mubarak, A.N.M.; Burgess, A.J.; Pyke, K.; Quick, W.P.; Murchie, E.H. (Frontiers in Plant Science, 2023)
Introduction Identifying rice (Oryza sativa) germplasm with improved efficiency of primary metabolism is of utmost importance in order to increase yields. One such approach can be attained through screening genetically diverse populations under altered environmental conditions. Growth or treatment under low carbon dioxide (CO2) concentrations can be used as a means of revealing altered leaf photorespiration, respiration and other metabolic variants. Methods We developed a pipeline for very high throughput treatment of gamma- and ethyl methanesulfonate- (EMS) induced mutant populations of IR64 rice seedlings at very low CO2 for 7 days. 1050 seedlings per batch at 5th leaf stage were exposed to 60 ppm CO2 for the first day and 30 ppm for the remaining three days. Following this, putative candidates were identified by measuring chlorophyll depletion using SPAD. Screening results showed a distinct difference between the mutants and the WTs. Results and discussion The mean chlorophyll loss in WTs ranged from 65% to 11% respectively, whereas in the mutant lines chlorophyll loss ranged from 0 to 100%, suggesting considerable phenotypic variation. Rice mutants with a reduced chlorophyll reduction (<10%) were identified as ‘Chlorophyll retention mutants’ (CRMs) under low CO2 stress. In total, 1909 mutant lines (14,000 seedlings) were screened for chlorophyll content under 30 ppm CO2, with 26 lines selected for detailed screening. These 26 putative candidates were self-seeded to produce an M5 generation, used to determine the genetic control of the altered response to low CO2. Gas exchange of light and CO2 response revealed that there were significant variations among photosynthetic properties in two selected rice mutants. The CO2 compensation points in the absence of photorespiration and leaf respiration rates were lower than the WTs and anatomical analyses showed that CRM 29 had improved mesophyll cell area. We propose that this approach is useful for generating new material for breeding rice with improved primary metabolism.